Potencial antitumoral e toxicidade do 5’-oxo-1’-fenil-1’,5’-diidro10h-espiro[acridina-9,2’-pirrol]-4’-carbonitrila (acmd) - Sousa, Tatyanna Kélvia Gomes de (2019)
Cancer is characterized by the uncontrolled growth of cells that can invade diverse tissues, being one of the most common causes of death in the world. Several problems in cancer therapy, such as low effectiveness, toxicity and development of resistance to treatment drive the search for new drugs. In this context, the antitumor potential of acridine derivatives is highlighted. The objective of this work was to investigate the toxicity and antitumor activity, as well as the possible mechanisms of action of a new acridine derivative 5'-oxo-1'- phenyl-1',5'-dihydro-10H-spiro[acridine-9,2'-pyrrole]-4'-carbonitrile (ACMD). In vitro antitumor activity was assessed by the MTT reduction assay in HL-60 cells and a 50% inhibitory concentration (IC50) of 9.8 μM was obtained. At concentrations of 11.4 and 22.8 μM, ACMD altered cell cycle progression, inducing G2/M arrest, as well as induced cell death by apoptosis, characterized by phosphatidylserine externalization, activation of caspases -3 and -7 and alteration of mitochondrial membrane potential. In the acute nonclinical toxicity test in mice, the 50% lethal dose (LD50) of ACMD was estimated around 1000 mg/kg (intraperitoneal, i.p.), considering guide no. 423 from the Organization for Economic Co-operation and Development (OECD) indicating low acute toxicity. Micronucleus assay in the peripheral blood of mice was performed to evaluate genotoxicity. It was observed that ACMD (300 mg/kg, i.p.) did not induce an increase in the number of micronucleated erythrocytes, suggesting low genotoxicity in vivo. In the evaluation of the in vivo antitumor activity in Ehrlich Ascitic Carcinoma (CAE) model, it was observed that after seven days of treatment with ACMD (25 or 50 mg/kg, i.p.) there was significant antitumor activity, considering all parameters evaluated (volume, mass and cell viability). Regarding the antitumor mechanisms of action, it was observed that ACMD (50 mg/kg) reduced peritumoral vascular microdensity, as well as CCL-2 chemokine levels. Also, increased levels of IL-12 and TNF-α cytokines were observed, indicating that ACMD was able to modulate the immune response against the tumor. Considering the vast role of oxidative stress in tumor propagation, the effect of ACMD was evaluated by means of the fluoridometric test of the 2,7-dichloro dihydrofluorescein diacetate (DCFH-DA). There was reduction of the oxidative stress level after ACMD (50 mg/kg) treatment, suggesting antioxidant effects. In addition, it also promoted nitrite reduction, an indicative of nitric oxide (NO) production, which is a key mediator involved in growth, angiogenesis and tumor metastasis processes. Among all toxicity parameters evaluated (metabolic, biochemical, hematological and histological parameters), it was observed that ACMD (50 mg/kg) induced changes in serum urea and creatinine concentration, as well as hemoglobin levels and hematocrit percentage, however, they were within normal limits. Together, the presented data indicates that ACMD induces antitumor activity in vitro, by interfering with cell cycle progression and inducing apoptosis, and in vivo, via antiangiogenic and immunomodulatory effects, besides has low in vivo toxicity in the evaluated models.